PENGARUH KONSENTRASI KEPEMILIKAN, UKURAN PERUSAHAAN DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN DALAM LAPORAN TAHUNAN STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI - LEO, JENNY (: 2303-1719)
The company's annual report is a management responsibility for the management of funds from creditors or the owners of capital. The company's annual report provide the financial and non-financial organizations related to the interaction with the physical and social environment.Disclosure supported by good corporate governace mechanisms need to be balanced between the positive information and negative information. This study aims to analyze whether ownership concentration variables, firm size, the composition of the board of commissioners, industry specialization Public Accountant and the audit committee affects the company's annual report disclosure index of manufacturing companies listed on the Indonesia Stock Exchange in 2008-2010. The results showed that firm size and composition commissioners effect to the company's annual report disclosure index. The concentration of ownership, industry specialization Public Accountant and the existence of an audit committee does not affect the company's annual report disclosure index